La Poste a la Trinidad - (:unkn) unknown (Unknown, 2011)
The postcard shows a female vendor giving a postman a pineapple. The flag that is printed in the corner, is the Red Ensign or "Red Duster" that originated in the early 17th century as a British ensign flown by the Royal Navy and later specifically by British merchantmen.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Merchants--Trinidad and Tobago; Flags--Great Britain; Postal service--Employees; Postal service--Trinidad and Tobago; Street vendors--Trinidad and Tobago; Uniforms--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago